E-017 Emergency Onyx embolization of avulsed basilar artery perforator following an endoscopic colloid cyst resection. (16th November 2010) - Turner, R; Lena, J; Chaudry, I; Turk, A
Abstract : Introduction: Endoscopic resection of a colloid cyst and third ventriculostomy is a well described neurosurgical procedure and is performed commonly. Inadvertent vascular injury can occur due to the limited peripheral field of view offered by the endoscope. We present a case of colloid cyst resection and third ventriculostomy where neurological decline occurred during anesthesia emergence and imaging demonstrated active basilar perforator extravasation on CT angiography (CTA) which was treated with emergency embolization. Case presentation: A 23-year-old man presented with headaches. He was found to have hydrocephalus due to a third ventricular colloid cyst. The patient underwent endoscopic resection and third ventriculostomy. During emergence, the patient was found to have a dilated right pupil. A ventriculostomy drain was placed and the patient underwent emergent CT/CTA which demonstrated intraventricular and pre-pontine hemorrhage with active extravasation. The patient underwent emergency angiography which demonstrated active contrast extravasation from a right P1 thalamoperforator. The vessel was catheterized and embolized with Onyx (eV3, Plymouth, Minnesota, USA) (Abstract E-017 figure 1 ). Results: There was immediate cessation of extravasation. The patient recovered and was following commands and getting out of bed. He had a complicated clinical course and subsequently developed meningitis and infarcts of his right middle cerebral artery territory and left basal ganglia from vasospasm. His prolonged hospital course concluded and the patient was discharged to home. Conclusion: Vascular injury is a rare but devastating complication of intracranial surgery. This is a unique case where emergent endovascular surgery immediately yielded an optimal angiographic result and provided the patient the best opportunity for recovery.